New Research on the Abbey of Le Bec in the Middle Ages
1 online resource (324 pages)
Keywords: This volume combines the results of recent excavations at Le Bec with fresh studies of documentary sources, breaking new ground in research on the organization of the monastic site and the cultural life of the community. By examining the abbey's prosperity in terms of its relations with its priories and its dealings with the powerful, especially its noble benefactors and the rulers of Normandy, this volume thus explains the unique importance of the abbey in the history of not only medieval Normandy, but also the Anglo-Norman world more broadly. Contributors are: Pierre Bauduin, Michaël Bloche, Grégory Combalbert, Fabrice Delivré, Gilles Deshayes, Jean-Hervé Foulon, Véronique Gazeau, Lindy Grant, Judith A. Green, Fabien Paquet, and Julie Potter.